2017
DOI: 10.1103/physrevlett.119.040502
|View full text |Cite
|
Sign up to set email alerts
|

Tensor-Network Simulations of the Surface Code under Realistic Noise

Abstract: The surface code is a many-body quantum system, and simulating it in generic conditions is computationally hard. While the surface code is believed to have a high threshold, the numerical simulations used to establish this threshold are based on simplified noise models. We present a tensor-network algorithm for simulating error correction with the surface code under arbitrary local noise. We use this algorithm to study the threshold and the subthreshold behavior of the amplitudedamping and systematic rotation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 34 publications
3
108
0
Order By: Relevance
“…We found that coherent physical errors result in logical errors that are partially coherent and therefore nonPauli, in agreement with recent numerical studies [14,15], but that the degree of coherence depends on the code distance and concatenation level. An analysis of the time to logical failure, based on a decoder optimized for independent Pauli errors, showed that the coherent part of the logical error is not important at fewer than  --( ) N 1 error correction cycles, where   1 is the rotation angle error per cycle for a single physical qubit and = N d n is the total number of qubits.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We found that coherent physical errors result in logical errors that are partially coherent and therefore nonPauli, in agreement with recent numerical studies [14,15], but that the degree of coherence depends on the code distance and concatenation level. An analysis of the time to logical failure, based on a decoder optimized for independent Pauli errors, showed that the coherent part of the logical error is not important at fewer than  --( ) N 1 error correction cycles, where   1 is the rotation angle error per cycle for a single physical qubit and = N d n is the total number of qubits.…”
Section: Resultssupporting
confidence: 92%
“…Another recent paper has reported diamond-distance logical error rates for surface codes up to distance d=10 for coherent physical errors [15]. That work also finds discrepancies between coherent physical errors and their Pauli twirl approximation that are consistent with coherent errors at the logical level.…”
Section: Introductionmentioning
confidence: 75%
“…Large codes can also be studied using tensor networks [17], although this requires a tensornetwork description of the code and is exponential in the code distance. An interesting and important open problem is to combine the current techniques with those of Refs.…”
Section: Discussionmentioning
confidence: 99%
“…(14), commuting R l to the left, using R † l R l = I and setting the result equal to eq. (17). Defining η(A, B) = ±1 for AB = ±BA, we obtain…”
Section: Effective Process Matrix At the Logical Levelmentioning
confidence: 99%
See 1 more Smart Citation